The prevalence and phenotypic manifestations of polycystic ovary syndrome (PCOS) among infertile Sudanese women: a cross-sectional study - Alawia N. Elasam; Mohamed A. Ahmed; Abdel B. A. Ahmed; Manal E. Sharif; Abdalla Abusham; Bahaeldin Hassan; Ishag Adam (BMC Women's Health, 2022)
Plain English summary Polycystic ovary syndrome (PCOS) is a global health problem associated with significant drawbacks during reproductive life. Few published studies have been conducted in Africa (including Sudan) addressing the clinical manifestations and phenotypic presentation of the disease. Therefore, we aimed to evaluate the clinical and biochemical presentation of the different PCOS phenotypes among infertile Sudanese women. A total of 368 infertile women with PCOS from a fertility center in Khartoum, Sudan, participated in the study. Clinical, hormonal, and ultrasonographic characteristics were described and compared between the four phenotype groups of PCOS. In this regard, Sudanese women uniquely expressed phenotype D as the most prevalent, and this does not match with the global distribution of PCOS phenotypes. Moreover, women with phenotype A were older and had high mean blood pressure, and a higher waist/hip ratio was observed among women with phenotype D. More epidemiological studies on this subject are needed in the region due to geographical, ethnic, and genetic variations.